ANALISIS KEBIASAAN BELAJAR SISWA KELAS XI SMA NEGERI 4 PALANGKA RAYA - Giusti, Gene; Sunaryo A.I; Suriatie, Mimi (Jurnal Bimbingan dan Konseling Pandohop, 2021)
Learning habits are methods or techniques that settle in students when receiving lessons, reading books, doing assignments, and setting time to complete learning activities. To get good learning achievement, students must have good study habits. The phenomenon obtained by researchers at SMA Negeri 4 Palangka Raya is (1) Students do not have structured learning habits, (2) many students do not understand the lessons conveyed in teaching and learning activities, and (3) Students are less active in asking questions if they do not understand with the material delivered by the teacher. This study aims to determine how the learning habits of students who excel in class XI SMA Negeri 4 Palangka Raya. This study uses a qualitative method. The population in the study were all students of class XI using a sample of 5 (five) students who have good learning achievement and study habits by looking at the student achievement index. In this study, researchers used 3 (three) data collection techniques, namely, interviews, observation, and documentation. The results of the study showed that class XI students at SMA Negeri 4 Palangka Raya have good study habits. This can be seen from students' good understanding of methods, techniques, skills, or efficient learning methods.